Mudharabah Pada Baitul Mal Wat Tamwil Sidogiri Cabang Pembantu Waru Sidoarjo - Shania Putri Ayu; Via Ratnasari; Dewi Audrynita; Affrido Galuh Mulyono (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2019)
Abstract: The Sidogiri Integrated Joint Business BMT Cooperative, abbreviated as